The association between affordable care act implementation and the prevalence of women having ever received a Pap smear - Eric M. Ganz; Benjamin Brown; Heather Smith; Lawren Wellisch; Megha Gupta; Stephen M. Wagner (Journal of Obstetrics and Gynaecology)
Background To assess if implementation of the 2010 Patient Protection and Affordable Care Act (ACA) was associated with changes in the prevalence of women having ever received a pap smear.Methods This study utilised the publicly available Centre for Disease Control National Survey of Family Growth (NSFG) data set. This was a serial cross-sectional study. The comparison groups were defined as women who received cancer screening and prevention interventions prior to full implementation of the ACA (2011–2013) and post full implementation (2017–2019). The primary outcome was self-reporting receipt of a Papanicolaou (Pap) smear. Secondary outcomes included HPV vaccination and mammogram rates. Anonymized patient information was collected from the nationally representative dataset, and analyses were performed utilising STATA 18.Results The two study cohorts obtained from the NSFG included women who responded in 2011–2013 (n = 5601), deemed to be ‘Pre-ACA implementation’ (Pre ACA), and those who responded in 2017–2019 (n = 6141) ‘Post-ACA implementation’ (Post ACA). The proportion of women who were 21 years and older and ever had a Pap smear in the Pre ACA group (96.0%) was higher than that of the Post ACA group (94.1%) (OR 0.66 (0.49–0.91)). In contrast, HPV vaccination rates rose, and mammogram rates remained stable in the Post ACA period.Conclusion A decrease in proportion of women ever having had a Pap smear despite implementation of health policies to increase access to preventive measures suggests further interventions to improve access to cervical cancer screening are warranted.